1969
DOI: 10.1111/j.1748-1716.1969.tb04450.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen and Umbilical Cord Clamping on Closure of the Ductus Arteriosus in the Guinea‐Pig and the Rat. Studies on Closure of the Ductus Arteriosus. VI

Abstract: Full‐term guinea‐pigs were delivered by caesarean section. Living fetuses with intact, or interrupted umbilical circulation were allowed to breathe, for periods of 5 min, air or nitrogen, or air followed by nitrogen. Animals sacrificed immediately on birth served as controls. Sacrifice was performed in liquid nitrogen.–Spontaneously delivered rats were either sacrificed immediately on birth or kept up to 4 hrs at 37° C in air or 8 c/c O2 in N2, before sacrifice in isopentane. cooled by dry ice. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An acute increase in oxygen tension causes perinatal pulmonary vasodilation (3,26), even while it results in constriction of the DA (1,5). Initial closure of the DA in response to an increase in PO 2 is caused by vessel constriction (14), whereas long-term closure is accomplished through cell migration, apoptosis (25), and cell proliferation (4,15,18).…”
mentioning
confidence: 99%
“…An acute increase in oxygen tension causes perinatal pulmonary vasodilation (3,26), even while it results in constriction of the DA (1,5). Initial closure of the DA in response to an increase in PO 2 is caused by vessel constriction (14), whereas long-term closure is accomplished through cell migration, apoptosis (25), and cell proliferation (4,15,18).…”
mentioning
confidence: 99%
“…Since ductal constriction can be elicited by the ad ministration of catecholamines or acetylcholine both in vivo and in vitro, it was considered of interest to analyze the role of autonomic transmitters in this phenomenon. Mature adrenergic terminals are abundant through out the wall of the human fetal ductus, as recently demonstrated with the Falck-Hillarp histochemical method [3], In the present study the wholebody freezing technique [5,7] was used since earlier studies had shown that this technique is sensitive enough to demonstrate that decrease in body temperature [8] and in oxygen saturation [6] delays the closure rate.…”
Section: Discussionmentioning
confidence: 99%